Strategi Pengembangan Agrowisata Edukasi Berbasis Komoditas Perkebunan Teh (Studi Kasus Agrowisata di Pusat Penelitian Teh dan Kina) - Bagaskara, Fadil; Shafa Fadhillah Hayah; Kralawi Sita; Aulia Rismala; Raihan Abdurrasyid (Pusat Penelitian Teh dan Kina, 2025)
One of the efforts to diversify the income of tea plantations amid increasing industrial challenges is the development of the agrotourism sector. This study aims to identify the conditions, development strategies, and roles of tea educational agrotourism at PPTK Gambung. The method used is qualitative descriptive with a SOAR (Strengths, Opportunities, Aspirations, Results) approach. The results of the study show that PPTK Gambung has strengths in supporting facilities, strategic location, and competent human resources. Opportunities include trends in nature tourism and the relevance of tea education for the community. Recommended strategies include enhancing employee capabilities, improving service systems, adding informative facilities, strategic partnerships, and active promotion. The implementation of these strategies is expected to improve the sustainability of the tea education program at PPTK Gambung.